2009
DOI: 10.1159/000264198
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus Infection Promotes Bax Redistribution to Mitochondria and Cell Death in HeLa Cells

Abstract: Background/Aims: Newcastle disease virus (NDV) is an avian paramyxovirus that has gained a lot of interest in cancer viro-therapeutic applications because of its ability to selectively induce apoptosis in human cancer cells. However, the underlying mechanisms by which NDV induces apoptosis in human cancer cells are still not entirely understood. Methods: In this study we examined the effect of a Malaysian velogenic strain of NDV, known as AF2240, on some elements of the intrinsic pathway of apoptosis. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 95 publications
(61 reference statements)
5
32
0
Order By: Relevance
“…To investigate whether their infectivity on another colorectal cancer cell line was also retained, we performed infections in HT29 cells. HT29 cells were previously shown to be susceptible to NDV oncolytic activities [19]. Spent culture media collected from the mock-infected SW480P cells were used to infect HT29 as described in the Materials and methods section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether their infectivity on another colorectal cancer cell line was also retained, we performed infections in HT29 cells. HT29 cells were previously shown to be susceptible to NDV oncolytic activities [19]. Spent culture media collected from the mock-infected SW480P cells were used to infect HT29 as described in the Materials and methods section.…”
Section: Resultsmentioning
confidence: 99%
“…The DIPs are characterized by their inability to infect cells on their own due to large genetic mutations [27]. This mNDV virus was also able to infect another colorectal cancer cell line, HT29 [19] albeit at lower cytotoxicity. This suggested that the mNDV maintained its infectivity in other cancer cells besides the parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, NDV has also gained a lot of interest in cancer virotherapy since it can selectively kill human cancer cells [5]. It has been shown that NDV induces apoptosis in cancer cells by activating the mitochondrial pathway [8,9]. The proteins of the Bcl-2 family are known central regulators of this pathway [10].…”
Section: Resultsmentioning
confidence: 99%
“…Many viruses have recently been found to activate Bax, including influenza A virus (49), respiratory syncytial virus (24), hepatitis B virus (44), hepatitis C virus (5), Theiler's murine encephalomyelitis virus (67), West Nile virus (55), rabies virus (36,74), poliovirus (2), rotavirus (48), and Newcastle disease virus (51). A common link for the ability of many different viruses to activate Bax may be induction of apoptosis via antiviral innate immunity pathways.…”
Section: Fig 9 Apoptosis Is Decreased At 9 Dpi In Baxmentioning
confidence: 99%